2020
DOI: 10.1177/1729881420925287
|View full text |Cite
|
Sign up to set email alerts
|

Research on abnormal object detection in specific region based on Mask R-CNN

Abstract: As an information carrier with rich semantics, image plays an increasingly important role in real-time monitoring of logistics management. Abnormal objects are typically closely related to the specific region. Detecting abnormal objects in the specific region is conducive to improving the accuracy of detection and analysis, thereby improving the level of logistics management. Motivated by these observations, we design the method called abnormal object detection in a specific region based on Mask R-convolutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Currently, several studies have attempted to develop systems for mask and abnormal object recognition One study [7] proposed a mask detector that uses a machine learning facial classification system to determine whether a person is wearing a mask in busy environments such as hospitals and markets. In detection method was proposed in the literature [12] for logistics management applications.…”
Section: State Council's Joint Prevention and Controlmentioning
confidence: 99%
“…Currently, several studies have attempted to develop systems for mask and abnormal object recognition One study [7] proposed a mask detector that uses a machine learning facial classification system to determine whether a person is wearing a mask in busy environments such as hospitals and markets. In detection method was proposed in the literature [12] for logistics management applications.…”
Section: State Council's Joint Prevention and Controlmentioning
confidence: 99%
“…In Nan, if there is neither energy theft nor meter failure, the total power provided by the energy supplier shall be approximately the same as the sum of energy consumption of metering users measured at each time interval [14][15].…”
Section: Theoretical Analysis Of Abnormal Power Consumption Datamentioning
confidence: 99%
“…The authors have created their dataset from the Qualnet simulator and have verified the results generated from the simulator using machine learning techniques. Xiong et al [23] have worked on the concept of machine learning and have shown its importance to validate the self-generated dataset from multiple scenarios, in converses the effective use of the information to assist in abnormal object detection based on the Mask R-CNN approach. The aim was to achieve the initial instance of the segmentation model through traditional R-CNN and extract the overlapping ratio of the results.…”
Section: Literature Surveymentioning
confidence: 99%